Determinants of rural household food security: a comparative analysis of African and Asian studies. (1st February 2013) - Bashir, Muhammad Khalid; Schilizzi, Steven
Abstract This paper reviews the determinants of rural household food security in Africa and Asia where more than 88% of the world's undernourished people live. A conceptual model is proposed on the basis of the three widely known components of food security: food availability, accessibility and utilisation. This model is used to select a total of 40 peer‐reviewed studies carried out over the last decade (20 each from Africa and Asia). A meta‐analysis technique is then used to identify which determinants of food security have been highlighted and how well the causality is demonstrated. Food availability is the most studied component in both regions, followed by food accessibility, while food utilisation is the most neglected component in these studies. © 2013 Society of Chemical Industry